The Effect of Education and Training on Employee Performance at PT. PERTAMINA (persero) - Lisda L Asi; Vatra Ayu Cahyani (Universitas Negeri Gorontalo, 2020)
The research objective was to find out to what extent the effect of education and training on employee performance at PT. PERTAMINA (persero) Fuel Oil Terminal of Gorontalo. The data collection was performed by distributing a questionnaire to respondents who have met the standard of the determined sample hence the research data were classified as primary data. The research samples were 30 people. The data were obtained from observation, interview, questionnaire, and documentation. Then, the data analysis used simple linear regression through the assistance of SPSS version 22 program. The findings of research showed that the value of determination coefficient R2 was 0,314 and it signified that 31,4% of employee performance at PT. PERTAMINA (persero) Fuel Oil Terminal of Gorontalo was affected by Education and Training program conducted by the company. Meanwhile, the rest employee performance for 68,6% was probably affected by other variables such as the compensation system, work culture, performance assessment, and others. This meant that a better Education and Training program conducted by the company would improve employee and company performance.